Motivation and Influencing Factors of English teachers’ Teaching Strategies in a Higher Vocational College - Xin, Liu; Singh, Charanjit Kaur Swaran (2024)
The literature looks at the complicated interactions among elements affecting English language teachers' teaching approaches and motivation in various educational environments. The studies underline how important extrinsic elements (salary, workload, institutional support) and intrinsic motivators (personal interest, altruism, perceived value of teaching) in forming teacher motivation and behavior. The study emphasizes the difficulties teachers encounter, including a lot of work, little support, and the necessity of enough tools and chances for professional development. The results highlight the need of matching teacher motivation with student needs and preferences in order to produce interesting and successful learning surroundings. To build a sustainable and vibrant teaching workforce, the studies support a multifarious approach to increase teacher motivation and professional growth including both intrinsic and extrinsic elements. Furthermore, emphasized by the research are the need of more research on the generalizability of results across many cultural and educational environments and the long-term effects of motivating strategies on teacher wellbeing and student learning outcomes.